2015
DOI: 10.12693/aphyspola.127.1052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Heat Treatments on the Solid Particle Erosion Behavior of Aluminum Alloy AA 7075 in Industrial Applications

Abstract: In this study, the solid particle erosion behavior of solutionized, articially aged (T6) and annealed aluminum alloy AA7075 has been investigated. The samples were eroded in solid particle erosion test equipment at 45• impingement angle and 75 m/s impingement velocity with 180 mesh garnet erodent particles. Afterwards, microstructures of solutionized, articially aged and annealed samples of AA7075 alloy were analyzed. In order to gure out the eect of ductility on erosion rates, the Brinell hardness of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Babu et al (2014) reported superplasticity of the friction stir processed Al-4.5 Mg-0.35 Sc-0.15 Zr alloy; Pradeep and Pancholi (2013) produced superplastic bulk area by multipass FSP in aluminum alloy; Smolej et al (2014) produced Superplasticity in friction stir processed Al-4.5 Mg-0.35 Sc-0.15 Zr alloy. The AA7075 alloy is high strength alloy among Al alloys which is extensively utilized for aerospace applications because of its high strength to weight ratio, good fracture toughness and high resistance to stress corrosion cracking (Karabay et al, 2015;Rometsch et al, 2014). AA7075 alloy always suffers from the poor joint strength due to of hot cracking, which inhibits the use of this alloy for practical applications (Gupta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Babu et al (2014) reported superplasticity of the friction stir processed Al-4.5 Mg-0.35 Sc-0.15 Zr alloy; Pradeep and Pancholi (2013) produced superplastic bulk area by multipass FSP in aluminum alloy; Smolej et al (2014) produced Superplasticity in friction stir processed Al-4.5 Mg-0.35 Sc-0.15 Zr alloy. The AA7075 alloy is high strength alloy among Al alloys which is extensively utilized for aerospace applications because of its high strength to weight ratio, good fracture toughness and high resistance to stress corrosion cracking (Karabay et al, 2015;Rometsch et al, 2014). AA7075 alloy always suffers from the poor joint strength due to of hot cracking, which inhibits the use of this alloy for practical applications (Gupta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fuyan et al 14 , Abd-Elrhman et al 15 , Patil et al 16 analyzed the effect of impact angle, Desale et al 17 , Lynn et al 18 , Liebhard et al 19 studied the effect of particle size , Dasgupta et al 20 , Grewal et al 21 analyzed the effect of sand concentration, Levy et al 22 analyzed the effect of particle shape, Biswas et al 23 , Franek et al 24 investigated the effect of particle impact energy, Sundararajan et al 25 analyzed the effect of slurry temperature and Gandhi et al 26 Okonkwo et al 27 Aquaro et al 28 studied the effect of impact velocity on wear rate and wear methodology. Limited studies were carried out to investigate the effect of material hardness on erosion wear rate and mechanism [29][30][31][32][33] . Most researchers carried out wear tests on ductile materials like aluminum or brass or they used very brittle materials like glass or ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation sequence of Al 2 O 3np /7075 composites has been reported to be: α-Supersaturated solid solution → GP Zones → η'-Transient phases (MgZn 2 ) → η-Equilibrium phases (MgZn 2 ) [31]. The GP zone phases are easiest to separate because the interface between GP zones phases with the matrix is coherent and the interfacial energy is low.…”
Section: Strengthening Mechanism and Hardnessmentioning
confidence: 99%